2008
DOI: 10.1002/jcp.21406
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine signaling involved in cell volume regulation: The role of released transmitters and plasma membrane receptors

Abstract: Cell volume regulation is a basic homeostatic mechanism transcendental for the normal physiology and function of cells. It is mediated principally by the activation of osmolyte transport pathways that result in net changes in solute concentration that counteract cell volume challenges in its constancy. This process has been described to be regulated by a complex assortment of intracellular signal transduction cascades. Recently, several studies have demonstrated that alterations in cell volume induce the relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 307 publications
1
35
0
Order By: Relevance
“…It is well known that tyrosine kinase receptors and specifically EGFR can be activated both by cell swelling or shrinkage [43,44] and can modulate numerous intracellular signaling pathways, such as focal adhesion kinase, mitogenactivated protein (MAP) kinase (MAPK), or phosphoinositide-3 kinase (PI3K) [45,46]. Our data indicate that EGFR signaling downstream of GABA A Rs promotes cell cycle entry of prominin þ precursors rather than a change in their cycle kinetics.…”
Section: Discussionmentioning
confidence: 68%
“…It is well known that tyrosine kinase receptors and specifically EGFR can be activated both by cell swelling or shrinkage [43,44] and can modulate numerous intracellular signaling pathways, such as focal adhesion kinase, mitogenactivated protein (MAP) kinase (MAPK), or phosphoinositide-3 kinase (PI3K) [45,46]. Our data indicate that EGFR signaling downstream of GABA A Rs promotes cell cycle entry of prominin þ precursors rather than a change in their cycle kinetics.…”
Section: Discussionmentioning
confidence: 68%
“…2A). I Cl,swell was activated upon exposure to increasing extracellular hypotonicity (17,25, and 33%, Fig. 2B, arrows).…”
Section: Resultsmentioning
confidence: 94%
“…Intracellular ATP and swelling-induced ATP release from cells has been identified as an important factor for RVD (25). Moreover, it has been shown that ATP binds to purinergic P2Y 2 receptors and activates TMEM16A (16).…”
Section: Volume 284 • Number 42 • October 16 2009mentioning
confidence: 99%
“…In articular chondrocytes, using the protein tyrosine phosphatase inhibitor sodium orthovanadate, it has been shown that activity of endogenous protein tyrosine kinases is required for the regulation of chloride currents [23]. The precise role of protein tyrosine kinase seems to vary according to the cell type, and diverse protein tyrosine kinases can exhibit antagonistic effects [24]. In this sense, the receptor protein tyrosine kinase epidermal growth factor promotes a swelling-activated chloride current in cardiac myocytes whereas the non-receptor protein tyrosine kinase Src inhibits it [25][26][27].…”
Section: Discussionmentioning
confidence: 99%